Součinitel výtoku rozměrově malých ostrohranných kruhových otvorů - Jinek, Josef (Vysoké učení technické v Brně. Fakulta stavební, 2013)
Tato práce pojednává o stanovení součinitele výtoku rozměrově malých ostrohranných kruhových otvorů ve dně při volném výtoku. Má za cíl ověřit znalosti v této problematice. Na základě měření byly stanoveny hodnoty součinitele výtoku pro různé průměry otvorů a tyto hodnoty byly porovnány s hodnotami doporučenými různými autory, jež jsou uvedeny v odborné literatuře. Na závěr práce bylo provedeno souhrnné zhodnocení.

This thesis deal with the determination of discharge coefficient of sharp-edged circular orifice in the bottom. Thesis is supposed to deepen knowledge of this subject and the main goal is to define discharge coefficient based on the done experiment. This measurement set values of coefficient for different orifice diameters and these values were compared with values published in specialized bibliography by different scientists. At the thesis end was made a summary thesis evaluation.
Discharge coefficient of dimensionally small sharp-edged circular orifices
Keywords: Ostrohranný kruhový otvor; paprsek; proudnice; volný výtok otvorem; součinitel výtoku.; Sharp-edged circular orifice; jet; stream line; free orifice flow; discharge coefficient.